The level of nurses’ knowledge of the prevention of nosocomial infections – a pilot study - Gąska, Izabela; Sygit, Katarzyna; Cipora, Elżbieta; Zukow, Walery; Karwat, Irena Dorota (Journal of Education, Health and Sport, 2017)
Introduction. A basic element in preventing and combating nosocomial infections is the medical personnel knowledge. It is up to health care workers to determine whether the hospital environment will be safe for both patients and those employed in this sector. The aim of the study was to present the level of nursing staff knowledge of nosocomial infections. Materials and methods. The research was carried out in the Podkarpackie Center of Cardiovascular Interventions in Sanok. The study group consisted of all nurses working in the Hemodynamic Department - 20 people. The tests were carried out using the diagnostic survey method. The research tool was the author’s questionnaire. Results. The nurses were aware that the scale of the problem of nosocomial infections was important. Almost all nurses rated their level of knowledge of hospital-acquired infections very well. However, the full definition of the term "nosocomial infections" was not given by about a quarter of respondents. In hospitals nurses did not always follow the rules of aseptic and antiseptic treatment. In addition, they did not see the need to educate patients and their families about the prevention of infections. Conclusions. Hospitals should carry out monitoring of nurses’ compliance with the procedures that are aimed at the elimination of ward infections and should consistently strive at their best to apply these procedures at their workplace. The ward staff should be involved in the education of patients and their families in the prevention of nosocomial infections.